Modernisme : van het Zwart Huis tot de Boekentoren - Bertels, Inge, 1976-; Strauven, Francis, 1942- (Tielt : Lannoo, 2008)
Watermaal-Bosvoorde, Sint-Agatha-Berchem, Sint-Lambrechts-Woluwe, Knokke, Ukkel, Elsene, Koekelberg, Antwerpenb, Boom, Tervuren, Brasschaat, Seraing, Gent, Zele, Oostende, Antwerpen, Anderlecht, Wilrijk, Deurne, Sint-Antonius-Brecht, Turnhout, Gentbrugge
Keywords: Modernisme